Compound-specific stable isotope analysis of amino acid nitrogen reveals detrital support of microphytobenthos in the Dutch Wadden Sea benthic food web - Riekenberg, Philip M.; van der Heide, Tjisse; Holthuijsen, Sander J.; van der Veer, Henk W.; van der Meer, Marcel T. J. (Frontiers in Ecology and Evolution, 2022)
The Wadden Sea is the world’s largest intertidal ecosystem and provides vital food resources for a large number of migratory bird and fish species during seasonal stopovers. Previous work using bulk stable isotope analysis of carbon found that microphytobenthos was the dominant resource fueling the food web with particulate organic matter making up the remainder. However, this work was unable to account for the trophic structure of the food web or the considerable increase in δ15N values of bulk tissue throughout the benthic food web occurring in the Eastern regions of the Dutch Wadden Sea. Here, we combine compound specific and bulk analytical stable isotope techniques to further resolve the trophic structure and resource use throughout the benthic food web in the Wadden Sea. Analysis of δ15N for trophic and source amino acids allowed for better identification of trophic relationships due to the integration of underlying variation in the nitrogen resources supporting the food web. Baseline integrated trophic position estimates using glutamic acid (Glu) and phenylalanine (Phe) allow for disentanglement of baseline variations in underlying δ15N sources supporting the ecosystem and trophic shifts resulting from changes in ecological relationships. Through this application we further confirmed dominant ecosystem support by microphytobenthos derived resources, although to a lesser extent than previously estimated. In addition to phytoplankton derived particulate organic matter and microphytobenthos supported from nutrients from the overlying water column there appears to be an additional resource supporting the benthic community. From the stable isotope mixing models, a subset of species appears to focus on microphytobenthos supported off recycled (porewater) N and/or detrital organic matter mainly driven by increased phenylalanine δ15N values. This additional resource within microphytobenthos may play a role in subsidizing the exceptional benthic productivity observed within the Wadden Sea ecosystem and reflect division in microphytobenthos support along green (herbivory) and brown (recycled/detrital) food web pathways.